The Effect of Venture Capital: Evidence From The Comparison of The Performance of VC-backed and non-VC-backed IPOs - Zhang, Le (2013)
This study explores the effect of venture capital has on the short-term operating performance of the UK IPOs during a period of 2000-2011. Four ratios are chosen to be the measurements of operating performance: return on assets, return on sales, operating cash flow on assets, operating cash flow on sales. By comparing the short-term operating performance between VC-backed IPOs and non-VC-backed IPOs, we draw a conclusion that VC-backed IPOs do not significantly outperform non-VC-backed ones, which is consistent with most research in the UK. Further analysis on the determinants of VC-backed and non-VC-backed IPOs for the operating performance is generated to give details. To be specific, size has a positive impact on the short-term operating performance on IPOs, while the impact from age is proved to be negative. Same as most research, price to book value positively affects the operating performance of IPOs regardless VC backing. Also, IPOs with higher market value tend to have higher operating return. The results of the two interaction variables, age*VC and size*VC, indicate that smaller and younger VC-backed IPOs are supposed to have higher operating return on assets. However for profit on sales, older ones tend to perform better. Interestingly, for both VC-backed IPOs and non-VC-backed IPOs, technology firms seem to have a poor operating performance in the subsequent two years after floatation.